Sei sulla pagina 1di 426

< λ u + µ v, w >= λ < u, w > +µ < v, w > u, v, w R n , λ, µ R

< u, v >=< v, u > u, v R n

< u, λ v + µw >= λ < u, v > +µ < u, w > u, v, w R n , λ, µ R

| u| 2 :=< u, u >= u T · u 0, u R n

u = 0

u =

λ, µ R,

u

u

1

n

,

v =

v

v

1

n

, w

=

w

w

1

n

R n

λ u + µ v =

λu 1 + µv 1

λu n + µv n

(λ u + µ v) T = (λu 1 + µv 1 , · · · , λu n + µv n )

< λ u + µ v, w >=

(λ u + µ v) T · w =

(λu 1 +

µv 1 , · · · , λu n + µv n ) ·

w

w

1

n

(λu 1 + µv 1 )w 1 + · · · + (λu n

λu 1 w 1 + µv 1 w 1 + · · · + λu n w n + µv n w n =

λ(u 1 w 1 + ··· + u n w n ) + µ(v 1 w 1 + ··· + u n w n ) =

λ u T · w + µ v T · w =

λ < u, w > +µ < v, w >

+ µv n )w n =

u =

u

u

1

n

,

v =

v

v

1

n

R n

u T = (u 1 , ··· , u n )

< u, v >=

u T · v =

(u 1 , ··· , u n ) ·

v

v

1

n

=

u 1 v 1 + ··· + u n v n = v 1 u 1 + ··· + v n u n = v T · u =< v, u >

u =

λ, µ R,

u

u

1

n

,

v =

v

v

1

n

, w

=

w

w

1

n

R n

λ v + µw =

λv 1 + µw 1 λv n + µw n

u T = (u 1 , ··· , u n )

< u, λ v + µw >=

u T · (λ v + µw ) =

(u 1 , ··· , u n ) ·

λv 1 + µw 1 λv n + µw n

   =

u 1 (λv 1 + µw 1 ) + ··· + u n (λv n + µw n ) =

λv 1 u 1 + µw 1 u 1 +

λ(u 1 v 1 + ··· + u n v n ) + µ(u 1 w 1 + ··· + u n w n ) =

λ u T · v + µ u T · w =

λ < u, v > +µ < u, w >

· · · + λv n u n + µw n u n =

< u, λ v + µw >=< λ v + µw,

u >=

λ < v, u > +µ < w,

λ < u, v > +µ < u, w >

u >=

u =

u 1

u

n

R n

u T = (u 1 , ··· , u n )

| u| 2 :=< u, u >= u T · u = (u 1 , ··· , u n ) ·

u 1 u 1 + ··· + u n u n = u 2

1 + ··· + u

2

n

u

u

1

n

=

0 u 2 + ··· + u n 0 | u| 2 0 0

1

2

| u| 2 = 0

< u, u >= 0

2

u 2 + ··· + u n = 0

1

u 1 = 0, ··· , u n = 0

u = 0

det( u T , v T ) = det( u, v) u, v R 2

det(α T , β T ) = det(α,

β) α,

β (R 2 )

det(λ u + µ v, w ) = λ det( u, w ) + µ det( v, w ) λ, µ R u, v, w R 2

det( u, v) = det( v, u) u, v R 2

det( u, λ v + µw ) = λ det( u, v) + µ det( u, w ) λ, µ R u, v, w R 2

u = u u

1

2

,

v

v = v

1

2

R 2

u T = (u 1 , u 2 ),

v T = (v 1 , v 2 )

det( u T , v T ) =

u 1 u 2 v

1

v

2

= u 1 v 2 u 2 v 1

det( u, v) =

u 1 v 1 u 2 v 2

= u 1 v 2 u 2 v 1

det( u T , v T ) = det( u, v)

α = (a 1 , a 2 ),

T = a a

α

1

2

β = (b 1 , b 2 ) (R 2 )

,

β T = b b 2

1

det(α T , β T ) =

a 1 b 1 a 2 b 2

= a 1 b 2 a 2 b 1

det(α,

β) =

a 1 a 2

b 1

b 2

= a 1 b 2 a 2 b 1

det(α T , β T ) = det(α,

β)

u = u

u

λ, µ R,

1

2

,

v

v = v

= λu 1 + µv 1

+ µv 2

λ u + µ v

λu

2

λu

λu

det(λ u + µ v, w ) =

1

2

+ µv 1 + µv 2

1

2

R 2

w

w

1

2

=

(λu 1 + µv 1 )w 2 (λu 2 + µv 2 )w 1 =

λu 1 w 2 + µv 1 w 2 λu 2 w 1 µv 2 w 1 =

λ(u 1 w 2 u 2 w 1 ) + µ(v 1 w 2 v 2 w 1 )

λ det( u, w ) + µ det( v, w ) =

λ

u

u

1

2

w

w

1

2

+ µ

v 1 v 2

v

1

v

2

w

w

1

2

=

λ(u 1 w 2 u 2 w 1 ) +

µ(v 1 w 2 v 2 w 1 )

det(λ u + µ v, w ) = λ det( u, w ) + µ det( v, w ) =

u = u u

1

2

,

v

v = v

det( u, v) =

u

u

1

2

v

v

1

2

R 2

1

2

=

u 1 v 2 u 2 v 1

det( v, u) =

v

v

1

2

u

u

1

2

= (u 2 v 1 u 1 v 2 ) = u 1 v 2 u 2 v 1

det( u, v) = det( v, u)

det( u, λ v + µw ) = det(λ v + µw,

u) =

(λ det( v, u) + µ det(w,

u)) =

λ(det( v, u)) + µ(det(w,

λ det( u, v) + µ det( u, w )

u)) =

det( u, v, w

)

u =

1

2

3


v =

,

3

2

1

  , w

=

0

4

10

w

λ u + µ v λ, µ R

det( u, v, w

)

u =

1

1

1

,

v =

3

2

1

, w

=

3

2

λ, µ R w

= λ u + µ v

1

2

3

3

2

1

0

4

10

det( u, v, w ) =

1

2

1

4

10

=

2

3

1

0

10

+ 3

2

1

4

0

4

=

1(20 4) 2(30) + 3(12) = 24 60 + 36 = 0

w = λ u + µ v

   =

0

4

10

λ + 3µ

2λ 2µ

3λ + µ


λ + 3µ = 0 2λ 2µ = 4

3λ + µ = 10


λ = 3µ

6µ 2µ = 4

9µ + µ = 10

λ = 3

µ = 1

µ = 1

w = 3 u + v

det( u, v, w ) =

1

2

1

1

4

1

1

1

1

3

2

1

3

1

2

4

2

1

4

=

+ 1

3

2

2

1

=

1(8 + 1) 1(12 2) + 1(3 + 4) = 7 10 + 1 = 2

w = λ u + µ v



 

2

1

4

=

λ + 3µ λ 2µ λ + µ

λ + 3µ = 2

λ 2µ = 1

λ + µ = 4

λ = 3µ 2

3µ 2 2µ = 1

3µ 2 + µ = 4

λ = 3µ 2

µ = 1

µ = 3

2

λ, µ R

w = λ u + µ v

u, v, w

λ, µ R

w

= λ u + µ v

u =

2

3

1

,

v =

1

2

3

  R 3

u

v

u

v

u v

u v

<

u, v >= u T · v = (2, 3, 1) ·

1

2

3

u v

=

w

0

1

3

u

<

u, w >= u T · w = (2, 3, 1) ·

0

1

3

  = 2 + 6 + 3 = 7

  = 0 + 3 3 = 0

=

w

0

3

2

v

< v, w >= v T · w = (1, 2, 3) ·

0

3

2

0 + 6 6 = 0

=

w

w

w

w

1

2

3

u < u, w

>= 0

<

u, w >= u T · w = (2, 3, 1) ·

w 1

w

w

3

2

  = 2w 1 + 3w 2 w 3

2w 1 + 3w 2 w 3 = 0 w 3 = 2w 1 + 3w 2


w 1 = s w 2 = t

w 3 = 2s + 3t

u

s

t

2s + 3t

=

s, t R

w

=

w

w 1

w

2

3

w

v < v, w

>= 0

<

v, w >= v T · w = (1, 2, 3) ·

w 1

w

w

3

2

  = w 1 + 2w 2 3w 3

w 1 + 2w 2 3w 3 = 0 w 1 = 2w 2 3w 3

w 1 = w 2 = s

w 3 = t

2s 3t

v

=

w

2s 3t

s

t

s, t R

=

w

w 1

w

2

3

w

u v < u, w >= 0 < v, w >= 0

< u, w >= u T · w = (2, 3, 1) ·

w 1

w

w

3

2

  = 2w 1 + 3w 2 w 3

< v, w >= v T · w = (1, 2, 3) ·

w 1

w

w

3

2

  = w 1 + 2w 2 3w 3

2w 1 + 3w 2 w 3 = 0 w 1 + 2w 2 3w 3 = 0

2w 1 + 3w 2 w 3 = 0 w 1 = 2w 2 3w 3

4w 2 6w 3 + 3w 2 w 3 = 0 w 1 = 2w 2 3w 3

w 1 = 2w 2 3w 3

w 2 = w 3 w 1 = 2w 3 3w 3


7w 2 7w 3 = 0

w 1 = t w 2 = t

w 3 = t

u v

=

w

t

t

t

 

t R

u v t = 1

=

w

1

1

1

u =

u

u

u

1

2

3

i

u

v

1

1

,

v =

j

u

v

2

2

k

u

v

3

3

u × v = v × u

v

v

v

1

2

3

, w

=

= u × v

w

w

w

1

2

3

  R 3

u × v u v

(λ u + µ v) × w = λ( u × w ) + µ( v × w ) λ, µ R u, v, w R 3

u v u + a v u

a

R

u, v, w

x R 3

x =

< x, u >

| u| 2

u +

<

x, v >

| v| 2

v +

< x, w >

|w | 2

w

< u, v×w >=< u× v, w >=

u

u

u

1

2

3

v

v

v

1

2

3

w

w

w

1

2

3

=

det( u, v, w )

u, v, w R 3

u × v =

i

u

u

2

3

v

v

2

3

i

j

k

u

u

u

1

2

3

j

v

v

v

1

2

3

u

u

1

3

=

v

v

1

3

+

k

u

u

1

2

v

v

1

2

=

(u 2 v 3 u 3 v 2 ) i (u 1 v 3 u 3 v 1 ) j + (u 1 v 2 u 2 v 1 ) k

i

j

k

u 1 u 2 u 3 v

3

v

1

v

2

= i

2

u 2 u 3 v

3

v

u 1

k

v 2 v 3

j

+ v 1

(u 2 v 3 u 3 v 2 ) i

u 1 ( jv 3 v 2 k) + v 1 ( ju 3 u 2 k) =

(u 2 v 3 u 3 v 2 ) i u 1 jv 3 +

u 1 v 2 k + v 1 ju 3 v 1 u 2 k =

j

k

u 2 u 3

=

(u 2 v 3 u 3 v 2 ) i (u 1 v 3 v 1 u 3 ) j + (u 1 v 2 v 1 u 2 ) k

j

u 1 u 2 u 3 v

v

i

1

v

2

k

3

= u × v

u × v =

i

u 2 v 2 u 3 v 3

i

j

k

u 1 v 1 u 2 v 2 u 3 v 3

=

j

u 1 v 1 u 3 v 3

+

k

u